Pro Visual Studio Team System Application Lifecycle Management - Rossberg, Joachim (Apress : Imprint: Apress, 2009)
You can have the best coders in the world working in your teams, but if your project management isn't up to scratch, your project is almost certain to be delayed, to come in over budget, and in some cases to fail entirely. By taking precise control of your application development process, you can make changes, both large and small, throughout your project's life cycle that will lead to better-quality finished products that are consistently delivered on time and within budget. Application lifecycle management (ALM) is an area of rapidly growing interest within the development community. Because its techniques allow you to deal with the process of developing applications across many areas of responsibility and across many different disciplines, its effects on your project can be wide ranging and pronounced. It is a project management tool that has practical implications for the whole team-from architects to designers, from developers to testers. This book focuses on the most powerful ALM tool available for the Microsoft .NET Framework: Visual Studio Team System (VSTS). It demonstrates the key concepts and techniques of ALM and illustrates how they can be achieved using the tools VSTS provides in a clear succinct style. After reading the book, you will understand how VSTS can be used to generate continuous meaningful reporting on your project's health for the decision makers on your team as well as for your project's sponsors.